Arterial stiffness in chronic kidney disease: causes and consequences. Issue 11 (20th April 2010) - Chue, Colin D; Townend, Jonathan N; Steeds, Richard P; Ferro, Charles J
Abstract : Chronic kidney disease is associated with elevated cardiovascular risk, and heart failure and arrhythmias are the biggest causes of cardiovascular death in this population. Increased arterial stiffness is a hallmark of chronic kidney disease and is associated with adverse alterations in cardiac structure and function that may predispose to an increased risk of cardiovascular death. These changes are already apparent in early kidney disease, which is highly prevalent in the developed world. The mechanisms underlying increased arterial stiffness in chronic kidney disease are undoubtedly complex, but an understanding is paramount to enable the development of novel therapeutic strategies to prevent or reverse this pathophysiology and therefore reduce the cardiovascular disease burden in this high-risk cohort.